Athlete personality characteristics and informal role occupancy in interdependent sport teams - Kim, J.; Gardant, D.; Bosselut, G.; Eys, M. (Psychology of Sport and Exercise, 2018)
Objectives: The current manuscript describes two studies that examined the relationship between athletes' big five personality characteristics and their occupancy of informal roles as identified by self-nominations and teammate-nominations. Design: A cross-sectional design was used to collect data on athlete personality and informal role occupancy. Method: Data were collected from 340 French athletes (Study 1) and 195 Canadian athletes (Study 2). In both studies, MANOVA were conducted to compare the personality scores of self-identified role occupants vs. non-role occupants. In Study 2, multiple linear regression analyses were also conducted to assess whether athletes' personality characteristics predicted the degree to which they were identified by their teammates as role occupants. Results: Across the studies and role identification methods (i.e., based on self- and teammate-nominations), team comedians appeared to be more extraverted and team distracters appeared to be less conscientious. Those viewed as the team mentors tended to be more emotionally stable, and those viewed as the team star players were less agreeable. Verbal and non-verbal informal leadership roles showed mixed associations with athlete personality characteristics. Openness to experience did not relate to informal role occupancy, and the occupancy of the team spark plug, enforcer, team player, social convener, cancer, and malingerer roles did not relate to athletes' big five personality characteristics. Conclusions: The current studies provide the first quantitative evidence that supports the theoretical propositions that athlete personality may underpin the processes by which athletes come to occupy informal roles on their teams.